Understanding the role of ecological divergence in the evolution of isolated populations in the Arremonops rufivirgatus species complex across Mesoamerica - Ronald A. Fernández-Gómez; David A. Prieto-Torres; Adolfo G. Navarro-Sigüenza; Luis A. Sánchez-González (BMC Ecology and Evolution)
Abstract Background The topographic complexity and wide range of environmental conditions of the Neotropical region have allowed the evolution of the most diverse avifauna in the world. Distributional patterns within this avian diversity mirror this complexity, and many species show allopatric distributions in environmentally continuous regions. Here, we used environmental variables and historical presence records to understand the evolution of the distribution of three isolated groups (Gulf, Pacific, and Yucatan Peninsula) of the Olive Sparrow (Arremonops rufivirgatus) species complex. We assessed the role of environmental factors underlying geographic distribution patterns in the complex based on ecological niche modeling and performed paleoclimatic reconstructions to assess distributional changes based on suitable areas during the Late Pleistocene. Results Niche similarity was not rejected in the Pacific/Yucatan comparison, but the Gulf/Pacific and Gulf/Yucatan comparisons showed niche differentiation. We found regions with low climatic suitability representing a biogeographic barrier for the Pacific and the Yucatan groups, but not for the Yucatan and the Gulf groups, suggesting that biotic factors, such as competition with ecologically similar species, may be involved in geographic isolation. Conclusions Our results suggest that allopatric distributions in the three groups within the A. rufivirgatus complex probably evolved due to biotic interactions with ecologically similar species in the relatively environmentally continuous areas across the Gulf Slope, but to range contractions leading to isolation in the Yucatan and the Pacific groups.